Effect of different sowing dates on yield of tomato genotypes (International Journal of Agricultural Research, Innovation and Technology, 2014)
The experiment was conducted at Agricultural Research Station, Thakurgaon, Bangladesh during October 2009 to March 2010 to observe the effect of sowing dates on yield of tomato genotypes. Three sowing dates viz. October 1, October 15 and October 30 were considered as factor A and tomato variety viz., BARI Tomato-2, BARI Tomato-3, BARI Tomato-4, BARI Tomato-9 and BARI Hybrid Tomato-4 considered as factor B. The experiment was laid out in RCBD (Factorial) with three replications. Early flowering (52.40 days) as well as early fruit harvesting (119.13 days) was occurred in October 1 sowing, where as sowing on October 30 resulted in delayed flowering (71.73 days) and fruit harvesting (140.67 days), respectively. Number of fruits per plant was also the highest (27.40) in October 1 sowing and the lowest (13.73) was in October 30 sowing. Seed sowing of October 1 was found better in respect of yield (74.75 tha-1) compared to October 15 (58.55 tha-1) and October 30 (24.60 tha-1) sowing. Among the variety, BARI Tomat-2 produced the highest (68.12 tha-1) marketable yield followed by BARI Tomato-9 (56.16 tha-1) and BARI Tomato-3 while BARI Tomato-4 gave the lowest (36.91 tha-1) marketable yield. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21090 Int. J. Agril. Res. Innov. & Tech. 4 (1): 40-43, June, 2014